Serum organic acid metabolites can be used as potential biomarkers to identify prostatitis, benign prostatic hyperplasia, and prostate cancer - He, Jinhua; Han, Zeping; Luo, Wenfeng; Shen, Jian; Xie, Fangmei; Liao, Liyin; Zou, Ge; Luo, Xin; Guo, Zhonghui; Li, Yuguang; Li, Jianhao; Chen, Hanwei (Frontiers in Immunology, 2023)
Background：Noninvasive methods for the early identify diagnosis of prostatitis, benign prostatic hyperplasia(BPH), and prostate cancer(PCa) are current clinical challenges. Methods：The serum metabolites of 20 healthy individuals and patients with prostatitis , BPH, or PCa were identified using untargeted liquid chromatography-mass spectrometry (LC-MS). Results：Organic acid metabolites had good sensitivity and specificity in differentiating prostatitis, BPH, and PCa. In addition, targeted LC-MS was used to verify the organic acid metabolites in the serum of a validation cohort. Three diagnostic models identified patients with PROSTATITIS: phenyllactic acid (area under the curve [AUC]=0.773), pyroglutamic acid (AUC=0.725), and pantothenic acid (AUC=0.721). Three diagnostic models identified BPH: citric acid (AUC=0.859), malic acid (AUC=0.820), and D-glucuronic acid (AUC=0.810). Four diagnostic models identified PCa: 3-hydroxy-3-methylglutaric acid (AUC=0.804), citric acid (AUC=0.918), malic acid (AUC=0.862), and phenyllactic acid (AUC=0.713). Two diagnostic models distinguished BPH from PCa: phenyllactic acid (AUC=0.769) and pyroglutamic acid (AUC=0.761). Three diagnostic models distinguished benign BPH from PROSTATITIS: citric acid (AUC=0.842), ethylmalonic acid (AUC=0.814), and hippuric acid (AUC=0.733). Six diagnostic models distinguished BPH from prostatitis: citric acid (AUC=0.926), pyroglutamic acid (AUC=0.864), phenyllactic acid (AUC=0.850), ethylmalonic acid (AUC=0.843), 3-hydroxy-3-methylglutaric acid (AUC=0.817), and hippuric acid (AUC=0.791). Three diagnostic models distinguished PCa patients with PROSTATITISA < 4.0 ng/mL from those with PSA > 4.0 ng/mL: 5-hydromethyl-2-furoic acid (AUC=0.749), ethylmalonic acid (AUC=0.750), and pyroglutamic acid (AUC=0.929). Conclusions：These results suggest that serum organic acid metabolites can be used as biomarkers to differentiate prostatitis, BPH, and PCa.